Tryptase and tumor angiogenesis - Ribatti, Domenico (Frontiers in Oncology, 2024)
Tryptases represent the most abundant constituent of human mast cells, involved in extracellular matrix degradation, contributing to wound healing and metastasis. Moreover, most recently, it has been demonstrated that tryptase is angiogenic both in vitro and in vivo. Tryptase-positive mast cell number increases parallelly with increased microvascular density in both solid and hematological tumors. The objective and the scope of this review article are to emphasize the important role of tryptase as one of the principal effectors of tumor angiogenesis mediated by mast cells. In this context, tryptase inhibitors may be considered a novel therapeutic approach in cancer treatment.